Inhibition of fibroblast growth factor receptor with AZD4547 mitigates juvenile nasopharyngeal angiofibroma. Issue 10 (14th July 2017) - Le, Tran; New, Jacob; Jones, Joel W.; Usman, Shireen; Yalamanchali, Sreeya; Tawfik, Ossama; Hoover, Larry; Bruegger, Dan E.; Thomas, Sufi Mary
Abstract : Background: Juvenile nasopharyngeal angiofibroma (JNA) is a benign tumor that presents in adolescent males. Although surgical excision is the mainstay of treatment, recurrences complicate treatment. There is a need to develop less invasive approaches for management. JNA tumors are composed of fibroblasts and vascular endothelial cells. We identified fibroblast growth factor receptor (FGFR) and vascular endothelial growth factor (VEGF) expression in JNA‐derived fibroblasts. FGFR influences fibroblast proliferation and VEGF is necessary for angiogenesis. We hypothesized that targeting FGFR would mitigate JNA fibroblast proliferation, invasion, and migration, and that targeting the VEGF receptor would attenuate endothelial tubule formation. Methods: After informed consent, fibroblasts from JNA explants of 3 patients were isolated. Fibroblasts were treated with FGFR inhibitor AZD4547, 0 to 25 μg/mL for 72 hours and proliferation was quantified using CyQuant assay. Migration and invasion of JNA were assessed using 24‐hour transwell assays with subsequent fixation and quantification. Mitigation of FGFR and downstream signaling was evaluated by immunoblotting. Tubule formation was assessed in human umbilical vein endothelial cells (HUVECs) treated with vehicle control (dimethylsulfoxide [DMSO]) or semaxanib (SU5416) as well as in serum‐free media (SFM) or JNA conditioned media (CM). Tubule length was compared between treatment groups. Results: Compared to control, AZD4547 inhibited JNA fibroblast proliferation, migration, and invasion through inhibition of FGFR and downstream signaling, specifically phosphorylation of ‐ p44/42 mitogen activated protein kinase (p44/42 MAPK). JNA fibroblast CM significantly increased HUVEC tubule formation ( p = 0.0039). Conclusion: AZD4547 effectively mitigates FGFR signaling and decreases JNA fibroblast proliferation, migration, and invasion. SU5416 attenuated JNA fibroblast‐induced tubule formation. AZD4547 may have therapeutic potential in the treatment of JNA.